'We will soon be dead': stigma and cascades of looping effects in a collaborative Ebola vaccine trial. Issue 1 (1st January 2021) - Alenichev, Arsenii
ABSTRACT: Can the careful implementation of global health research reduce the stigmatization of involved human subjects? This study analyses stigma in an Ebola vaccine clinical trial in West Africa that deployed complex community engagement strategies including a sensitization component. Qualitative research found that stigma against trial subjects manifested in various forms beyond the reach of these anti-stigma interventions. Drawing on and advancing Hacking's notion of 'looping effects', this paper argues that stigma was a product of a wider socio-historical context beyond the control of community-based interventions. This case prompts global health practitioners to think through the limitations of community-based interventions in practice.